Derivational Patterns in Slavic Languages - Tadić, Marko (2013)
The topic of this talk is not not relying on a particular morphological theory framework, but presents a set of empirically collected data and an attempt to explain their relations at morphological and semantic level, first within one Slavic language (Croatian), and then applied to other Slavic langauges. In this respect it is a work in progress. While developing Croatian Wordnet (CroWN) using expanded model (translation of the Princeton Wordnet, PWN), we run into a discrepancy between English literals and synsets and their Croatian translation equivalents. Namely, the verbal aspectual pairs were pointed out as one of the main causes of trouble. This led us to research and try to solve this problem in a way applicable for this particular language resource. Since all verbs in Croatian are always morphologically marked for aspect (perfective, imperfective, or bi- aspectual), the majority of English verbs from PWN have two or more translation equivalents in Croatian (depending on the aspect). This complicates the structure of CroWN as well as inter- lingual index between PWN and CroWN. Different Slavic wordnets solved this problem in different manner, but by investigating the distribution od 19 Croatian verbal prefixes, we modelled their meaning as purely aspectual with four possible additional main Akzionsart meanings. This approach led us to the idea that probably the best way to describe relations or processes in derivation, that demonstrate regularity in form and meaning, could be the usage of pattern- based templates. In this respect we wanted to find whether the derivational pattern-approach could be applied in other processes and not just verbal prefixation. Following Pala & Hlavačkova (2007), this pattern-based approach can be applied to derivational processes forming other POSs as well, and applied to Wordnet relations. By introducing 10 basic derivational patterns and their semantic labels, a framework for describing derivational nests has been provided. We would also like to demonstrate how this derivative patterns approach can be applied and observed cross-lingually in other Slavic languages such Czech, Slovak, Slovenian, Croatian, Polish and Russian, as it sometimes reveals a remarkable correspondence. This derivational information introduced back into wordnet could enrich its structure and help us position derivation to the place it deserves, both in linguistic description and language resources and tools.